2011
DOI: 10.1200/jco.2011.35.0660
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Placebo-Controlled Trial of Carboplatin and Paclitaxel With or Without the Vascular Disrupting Agent Vadimezan (ASA404) in Advanced Non–Small-Cell Lung Cancer

Abstract: The addition of ASA404 to carboplatin and paclitaxel, although generally well tolerated, failed to improve frontline efficacy in advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(188 citation statements)
references
References 17 publications
(5 reference statements)
3
183
0
2
Order By: Relevance
“…5,6‐dimethylxanthenone (DMXAA or ASA404), flavone acetic acid analog, is a potent vascular disrupting agent that has completed multiple clinical trials, including a large scale phase III trial of carboplatin and paclitaxel with or without ASA404 in advanced non‐small‐cell lung cancer (NSCLC) 165, 166, 167, 168, 169…”
Section: Combining Phototherapy With Novel Anti‐cancer Agentsmentioning
confidence: 99%
“…5,6‐dimethylxanthenone (DMXAA or ASA404), flavone acetic acid analog, is a potent vascular disrupting agent that has completed multiple clinical trials, including a large scale phase III trial of carboplatin and paclitaxel with or without ASA404 in advanced non‐small‐cell lung cancer (NSCLC) 165, 166, 167, 168, 169…”
Section: Combining Phototherapy With Novel Anti‐cancer Agentsmentioning
confidence: 99%
“…In addition, mice that completely rejected tumors were protected against a rechallenge with the same tumor cell line, implying the generation of an immunological memory [107]. Although DMXAA failed in a phase III clinical trial of non-small cell lung carcinoma [108], now it is well known that this was due to its inability to bind human STING. New agents are being developed that engage human STING.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…A recent phase III trial of DMXAA in combination with carboplatin-paclitaxel chemotherapy for advanced non small cell lung cancer showed no improvement in progression free survival compared to chemotherapy alone, although DMXAA was well tolerated [178].…”
Section: Dmxaamentioning
confidence: 99%
“…In contrast, DMXAA is a vascular disrupting agent that induces apoptosis in tumour endothelial cells, resulting in collapse of the tumour vasculature and thus tumour hypoxia and necrosis [177]. With DMXAA treatment at 1800mg/m 2 , the dose used in phase III clinical trials in combination with chemotherapy [178], a phase I trial of single agent DMXAA reported an estimated plasma C max of 1000µM [179]. A DMXAA dose range of 0 -300µg/ml was therefore initially studied.…”
Section: Vascular Disrupting Agentmentioning
confidence: 99%